Application of microfluidic biochips for male fertility assessment - Yu, Tian (Nanyang Technological University, 2020)
Infertility is a world-wide issue that impacts almost a tenth of total number of families. About a half of the infertility cases are contributed by males. Therefore, assessment of male fertility, which is indicated by percentage of fertile sperms, becomes an important clinic demand. In the past decade, the advancement of microfluidic biochip technology has suggested more instant and convenient designs to meet the clinic need. This report aims to validate a fabricated microfluidic biochip that utilizes capillary flow to filter fertile sperms through a channel filled with vertical pillars. The validation is done through simulation with COMSOL software and experimental method with actual chips. Further comparison between the simulation and experiment results is also discussed. With further research, the viability of using microfluidic biochip to assess male fertility could be achieved in the future.